The impact of symmetry design of intangible cultural heritage souvenir on tourists’ aesthetic pleasure - Liu, Yuqing; Chen, Meiyi; Wang, Qingsheng (Frontiers in Psychology, 2022)
Souvenirs play an important role in tourism development. They act not only as mementos, enabling tourists to relive and retain the memory of a particular journey, but also as main income sources for tourism destinations and stakeholders. Many intangible cultural heritages (ICH) have been developed into souvenirs, especially products made by traditional craftsmanship. ICH souvenirs facilitate cultural value that is understandable to tourists, who appreciate the design of the ICH souvenirs and their contributions to a pleasure and memorable journey. Based on the theory of beauty and the preference-for-prototypes theory, this study explored how symmetry design of ICH souvenirs influences tourist’s aesthetic pleasure. As ICH souvenirs development is a commercialization process, and over-commodification would lead to cultures being lost and tourists’ disappointment, the authenticity concept is applied in order to address over-commodification. Thus, this study analyzed the moderating role of tourists’ authenticity perception of ICH souvenirs. Two lab-based between-subjects design experiments were employed to test the proposed hypotheses. Data analysis entailed multiple regression analysis, one-way ANOVA, and two-way ANOVA. The findings showed that symmetry of ICH souvenir design had a positive impact on tourists’ aesthetic pleasure. Under the symmetric-design condition, tourists’ typicality perception of ICH souvenirs positively mediated the main relationship, while under the asymmetric-design condition, tourists’ novelty perception had a negative mediating effect. The moderated mediation effects were in accord with hypotheses to some extent; at a relatively high level of authenticity perception (above mean value), the indirect effect of symmetry on aesthetic pleasure via typicality perception increased as authenticity perception rose; at a relatively low level of authenticity perception (under mean value), the indirect effect of symmetry on aesthetic pleasure via novelty perception declined as authenticity perception rose. This study identified critical factors influencing tourists’ aesthetic pleasure with ICH souvenirs, and it revealed the internal influencing mechanisms and moderating effects under different design conditions. These findings give some insights to ICH practitioners for using souvenir design to improve tourists’ aesthetic pleasure.